2009
DOI: 10.1128/aem.01476-08
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bacteriocinogenic Strains of Saccharomyces cerevisiae Heterologously Expressing and Secreting the Leaderless Enterocin L50 Peptides L50A and L50B from Enterococcus faecium L50

Abstract: A segregationally stable expression and secretion vector for Saccharomyces cerevisiae, named pYABD01, was constructed by cloning the yeast gene region encoding the mating pheromone ␣-factor 1 secretion signal (MF␣1 s ) into the S. cerevisiae high-copy-number expression vector pYES2. The structural genes of the two leaderless peptides of enterocin L50 (EntL50A and EntL50B) from Enterococcus faecium L50 were cloned, separately (entL50A or entL50B) and together (entL50AB), into pYABD01 under the control of the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The enterocin L50-producing strain E. faecium L50 (8) Molecular techniques and enzymes. Established protocols were employed for all DNA manipulations, including PCR amplifications, restriction endonuclease digestions, ligations, and transformations, as previously described (3,24). Oligonucleotide primers (Table 2) were obtained from Sigma-Genosys Ltd. (Cambridge, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The enterocin L50-producing strain E. faecium L50 (8) Molecular techniques and enzymes. Established protocols were employed for all DNA manipulations, including PCR amplifications, restriction endonuclease digestions, ligations, and transformations, as previously described (3,24). Oligonucleotide primers (Table 2) were obtained from Sigma-Genosys Ltd. (Cambridge, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…While enterocin P is secreted by the Sec translocase (30), it has been suggested that the enterocin L50 peptides are secreted by a dedicated ABC transporter, as demonstrated for enterocin Q and other leaderless bacteriocins (12,20,43). Although individual EntL50A and EntL50B possess some antimicrobial activity on their own, with EntL50A being the most active, a clearly synergistic effect is observed when both peptides are combined (2,3,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…cloned into recombinant S. cerevisiae (2,37,41) and P. pastoris (3,4,21,36) hosts have been produced with variable success regarding its secretion and functional expression. Recombinant LAB, heterologous producers of EntA, also show higher EntA production (1.5-to 18.5-fold) than E. faecium T136, and the EntA they produce shows higher antimicrobial activity (1.5-to 6.6-fold) than that of the EntA produced by E. faecium T136, although the specific antimicrobial activity of the EntA produced was lower than that deduced from its production (10,32).…”
mentioning
confidence: 99%